Sorghum RILs Segregating for Stay‐Green QTL and Leaf Dhurrin Content Show Differential Reaction to Stalk Rot Diseases. Issue 6 (6th October 2016) - Adeyanju, Adedayo; Yu, Jianming; Little, Christopher; Rooney, William; Klein, Patricia; Burke, John; Tesso, Tesfaye
Abstract : The association between postflowering drought tolerance and the stay‐green phenotype in sorghum [ Sorghum bicolor (L.) Moench] is well established. Recent studies link the stay‐green phenotype with levels of dhurrin and soluble sugars in the leaves. Postflowering drought response has always been associated with stalk rot resistance, especially charcoal rot. However, apart from the common knowledge that charcoal rot requires a dry environment, the mechanism governing these associations is not clear. The objectives of this study were to (i) determine the effects of major stay‐green ( stg ) quantitative trait loci (QTL) on response to infection by two stalk rot pathogens, Macrophomina phaseolina and Fusarium thapsinum, and (ii) examine the possible relationship between levels of dhurrin and soluble sugar in the leaves and response to stalk rot diseases. Fourteen genotypic groups derived from the Tx642 × Tx7000 recombinant inbred line (RIL) population carrying a combination stg QTL were evaluated under three environments in four replications. The results revealed that stg QTL have variable effects on severity of stalk rot diseases. Genotypes carrying either stg 1 or stg 3, or their combination stg 1+3 expressed high levels of resistance to M. phaseolina . But, resistance to F. thapsinum required a combination of stg 1 and stg 3. Other stg QTL blocks, such as stg 2 and stg 4, did not have an effect on stalk rot resistance caused by either pathogen. Furthermore, stalk rot resistance had no significant association with levels of dhurrin and soluble sugars in the leaves.